1986
DOI: 10.1007/bf01645203
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ofloxacin and theophylline alone and in combination

Abstract: The pharmacokinetic interactions of ofloxacin (2 X 200 mg) and theophylline (3 X 200 mg) were investigated in 12 healthy volunteers over a period of two weeks. In the first week, theophylline was given over five days to reach a steady state. In the second week, the combination of theophylline and ofloxacin was applied. Cmax, tmax, AUC0-8, the serum elimination constant and serum half-life of theophylline were not changed when theophylline was given alone or in combination with ofloxacin. The kinetic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…Levels in serum increase, and dosage adjustment of theophylline could be necessary (19,38). Antacids may delay the absorption and decrease the amount absorbed (42).…”
Section: Commentsmentioning
confidence: 99%
“…Levels in serum increase, and dosage adjustment of theophylline could be necessary (19,38). Antacids may delay the absorption and decrease the amount absorbed (42).…”
Section: Commentsmentioning
confidence: 99%
“…Coadministration of theophylline with three structurally related compounds, enoxacin, pefloxacin, and ciprofloxacin, has been reported to increase theophylline concentrations and cause toxicity (2,8,11,(13)(14)(15)(16); coadministration with nalidixic acid, another quinolone, does not (16). Ofloxacin has been reported to decrease or have no effect on theophylline clearance (3,5,16). It has been postulated that the 4-oxoquinolone metabolites rather than the parent drug cause the drug interaction (6, 16).…”
mentioning
confidence: 99%
“…The in vivo experiments in this study showed that ENX markedly and NFLX slightly prolonged the T1 /2 of theophylline in rats, but OFLX did not affect it. Many investigators have reported a similar result in human sub jects, that ENX markedly raised the plasma theophylline concentration and prolonged its T1 /2, whereas NFLX and OFLX had little or no effect on the pharmacokinetics of theophyl line (1)(2)(3)(4)(5)(6)(7)(8). Sekine et al (12) and Okazaki et al (26) have shown similar results in rats con cerning ENX and OFLX.…”
Section: Discussionmentioning
confidence: 72%
“…Since then, many investigators have demonstrated that ENX raises the plasma theophylline concentration and prolongs its elimination half-life (T1 /2). In contrast, other new quinolones, such as norfloxacin (NFLX) and ofloxacin (OFLX), have no or only a slight effect on the pharmacokinetics of theophyl line (2)(3)(4)(5)(6)(7)(8). It appears that the increase in the plasma theophylline concentration is due to a reduced metabolic clearance of theophylline in the liver induced by ENX, while NFLX and OFLX seem to have little effect on drug metabolizing activity in the liver.…”
Section: Acceptedmentioning
confidence: 99%
See 1 more Smart Citation